MEMBANGUN SINERGI ANTARA CIVITAS AKADEMIKA DENGAN SEKOLAH DALAM MENUMBUHKAN DIGITAL ENVIRONMENT ERA 5.0 - Teuku Muhammad Syauqi; Fathiah Fathiah; Eliana Eliana; Nelliraharti Nelliraharti; Murnia Suri; Muhammad Muhammad; Vilzati Vilzati; Syarifah Mauli Masyithah (Bajang Institute, 2023)
xxx